Adsorption of nitrate from interflow by the Mg/Fe calcined layered double hydroxides. (22nd July 2022) - Chu, Liquan; Zhang, Chaojie; Yu, Jing; Sun, Xu; Zhou, Xuefei; Zhang, Yalie
Abstract: Nitrate loss in interflow caused serious nitrate pollution of neighboring water bodies in the purple soil region of China's Sichuan Province. In this study, Mg/Fe(Al)-calcined layered double hydroxides (Mg/Fe(Al)-CLDHs) with varied Mg/Fe(Al) ratios were synthesized for nitrate removal from interflow, and 3:1 Mg/Fe CLDH exhibited the best adsorption performance. The effects of initial pH, adsorbent dosage and co-existing anions on the adsorption performance were investigated by batch experiments. The best-fitting kinetic and isothermal models for nitrate adsorption were the pseudo-second-order model and Freundlich model, respectively, indicating that the adsorption process was a physical-chemical multilayer process. The maximum adsorption capacity of nitrate was 73.36 mg/g, which was higher than that of many other commonly used adsorbents. The adsorbents were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscope (TEM) and Brunauer–Emmett–Teller (BET) techniques, and the XRD and FT-IR results revealed that the adsorption mechanism involved original layered structure reconstruction and ion-exchange interaction. Under the coexistence of SO4 2− and Cl −, 75.63% nitrate in interflow could be removed after 6 h of adsorption. Overall, the synthesized Mg/Fe CLDH is an effective and low-cost nitrate adsorbent for in-situ nitrate removal. HIGHLIGHTS: Mg/Fe calcined layered double hydroxides were synthesized for nitrate adsorptive removal. The best-fitting kinetic model and isothermal model for nitrate adsorption were the pseudo-second-order model and Freundlich model, respectively. The adsorption mechanism involved original layered structure reconstruction and ion-exchange interaction. 75.63% nitrate was removed from interflow water after 6 h of adsorption. Graphical Abstract